Pencegahan Infeksi dan Transfer Mikroorganisme - Aldona Diva Aurelia; Alma Danita; Echa Ananta Perdani; Evanda Gita Septiana; Rina Fitriani; Via Aulia Ramadani; Liss Dyah Dewi Arini (INDO PUBLISHING, 2025)
This article aims to synthesize the latest scientific evidence on the main ways microorganisms (bacteria, viruses, fungi) spread and assess the most important infection prevention strategies. This study used a narrative literature review method. Articles were searched in scientific databases such as PubMed, Google Scholar, and Scopus, as well as guidelines from global health organizations such as the WHO and the CDC. Keywords used included